Association of dietary intake of saturated fatty acids with hypertension: 1999–2018 National Health and Nutrition Examination Survey - Gou, Ruoyu; Gou, Yufan; Qin, Jian; Luo, Tingyu; Gou, Qiannan; He, Kailian; Xiao, Song; Li, Ruiying; Li, Tingjun; Xiao, Jie; Chen, Ziqi; Chen, Yulu; et al. (Frontiers in Nutrition, 2022)
Objective This study aimed to assess the relationship between the dietary intake of saturated fatty acids (SFAs) and its subtypes (C4:0, C6:0, C8:0, C10:0, C12:0, C14:0, C16:0, and C18:0) and hypertension. Design, participants, and methods Adults aged 20 years and older based used the U.S. Health and Nutrition Survey (1999–2018) were used as participants. Two averages of 24 h dietary recall data were obtained for weight-adjusted continuous cross-sectional analysis. Two 24-h recall interview data means were obtained for weight-adjusted continuous cross-sectional analysis. A logistic regression model was used to estimate the weighted odds ratio (OR) and its 95% confidence interval (CI) for hypertension. Results The study included 7,222 respondents over 20 years of age with a hypertension prevalence of 23.2% and a significant difference in the dietary intake of carbohydrates among patients with hypertension. Dietary intake of nutrients was more in men than in women with hypertension. After adjusting for confounders, adjusting for nutrients, and reducing covariance among nutrients, the OR (95% CI) for women’s dietary intake of SFAs, C14:0, C16:0, C18:0 fourth quartile, and C14:0 third quartile were 0.57 (0.34, 0.95), 0.57 (0.34, 0.95), 0.57 (0.34, 0.95), 0.57 (0.34, 0.95), and 0.57 (0.34, 0.95), respectively, which may be a risk factor for hypertension. In older (≥65, years) respondents, the OR (95% CI) for dietary intake of SFAs, C4:0, C14:0, C16:0 fourth quartile, and C12:0 third quartile were 0.42 (0.21, 0.86), 0.46 (0.22, 0.95), 0.39 (0.18, 0.85), 0.38 (0.17, 0.84), and 0.45 (0.20, 0.99), respectively, which may be a protective factor for hypertension. Conclusion The study was based on the American Health and Nutrition Examination Survey, and a strong correlation was found between dietary intake of SFAs, C14:0, C16:0, and C18:0 and hypertension in women (dietary intake of SFAs, C4:0, C12:0, C14:0, and C16:0) and middle-aged and older adults (dietary intake of SFAs, C4:0, C12:0, C14:0, and C16:0). In addition, dietary nutrient intake should be carefully selected for the rational prevention of hypertension.